Anti-diabetic Potential of a Stigmasterol From the Seaweed Gelidium spinosum and Its Application in the Formulation of Nanoemulsion Conjugate for the Development of Functional Biscuits - Poulose, Navya; Sajayan, Arya; Ravindran, Amrudha; Chandran, Ambili; Priyadharshini, G. Balasubramanian; Selvin, Joseph; Kiran, G. Seghal (Frontiers in Nutrition, 2021)
The seaweed Gelidium spinosum was selected for the extraction of phytosterol by the Soxhlet method. The extracted phytosterol was chemically characterized as stigmasterol using Fourier-transform infrared spectrometry and gas chromatography–mass spectrometry analysis. The antioxidant and α-amylase inhibitory activity of stigmasterol has been confirmed by in vitro assays. The in vivo studies demonstrated an anti-diabetic effect in streptozotocin (STZ)—induced hyperglycemic rats. Biochemical analysis showed administration of stigmasterol reduced the blood sugar, urea, and creatinine level. The stigmasterol was then nano-emulsified and incorporated into dough for biscuit formulation. The stigmasterol incorporated biscuit showed higher proximate values, low moisture content, lighter color and the textural property revealed lower hardness. Sensorial results showed acceptability when compared to the control. This study demonstrated the stigmasterol reduced hyperglycemic effects and therefore could be used as a supplement in diets for diabetic patients.